PENGEMBANGAN MEDIA PEMBELAJARAN WEBTOON UNTUK MENANAMKAN SIKAP TOLERANSI DI SEKOLAH DASAR - Siti Aliah; Zulfa Safira Firdausy; Arita Marini (Bajang Institute, 2023)
According to hasan alwi (2002), character is “a mental, moral, or ethical quality that distinguishes one person from another.” Whereas according to coon (zubaedi, 2011: 8), character is “a subjective assessment of one’s personality as to a personality that is acceptable to or unacceptable to society.” That character would form motivation by a dignified process. Good character includes care and action based on ethical values, and it includes both the cognitive, emotional, and behavioral aspects of moral living (jamal ma ‘myrrh asmani, 2011: 27). Indonesia is a country with many diversity ranging from ethnic, cultural, and religious diversity. As Indonesia has so much diversity, tolerance has become an important thing for everyone including elementary school students, a growing and growing tolerance attitude in the family, society and school environment will avoid such issues as discord and conflict caused by diversity. A growing and well-developed attitude of tolerance will result in harmony within the environment. The education of character will need to be applied to the Indonesian public. Therefore, to instill character education especially the nature of tolerance in elementary school students, which requires media that can interest students.